(untitled) (Research, Society and Development, 2023)
The scientific article in question addresses the role of Public International Law and Human Rights in contemporary times, focusing on the protection of refugees, in order to explore the role of international treaties in the implementation of human rights, highlighting their connection to signatory States. In this way, the research aims to understand how Public International Law and international organizations act to protect human rights in contemporary times, especially in relation to refugees. The research is justified by the importance of human rights after the Second World War and the growing issue of refugees around the world. The need for Brazil to get involved in global issues related to human rights also stands out. The discussion on refugees is crucial given the current crisis in Venezuela and elsewhere, and turning a blind eye to this issue could compromise human rights gains. The methodology includes a descriptive and qualitative approach, based on bibliographical research and analysis of international treaties and conventions. The study hopes to contribute to the theoretical understanding of the topic, since the protection of Human Rights and the reception of refugees are global challenges that require a cooperative approach and respect for the international legal system, aiming to promote human dignity.